Effectiveness of Ruangguru Application as Communication Medium in Online Tutoring among HighSchool Students in Medan - Toruan, Rachel Mia Lorenza Lumban; Asmara, Sakhyan; Zulkarnain, Iskandar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to analyze the meaning of tutoring by high school students in Medan, analyze the effectiveness of Ruang Guru application as a communication medium in online tutoring activities among high school students in Medan, and analyze cognitive, affective and psychomotor changes in high school students in Medan after taking online tutoring through Ruang Guru application. This study uses qualitative methods with research subjects from various circles, namely high school students, parents, high school teachers and two triangulation informants, namely master teacher or tutor and communication observer. The results showed that Ruang Guru application was effective as a medium of communication in online tutoring activities among high school students in Medan. This can be seen from the effectiveness of communication and the effectiveness of Ruang Guru application. The effectiveness of communication is viewed from communicators, messages, media, communicants, and effects. The effectiveness of Ruang Guru application is viewed from the aspect of tasks and functions, and the aspect of plan or program. The change that was gotten by students who subscribe to Ruang Guru is changes from the cognitive aspect, while the affective and psychomotor aspects have not been seen in students. The students also understand about the meaning of tutoring.